Histological demonstration of BSEP/ABCB11 inhibition in transient neonatal cholestasis: a case report - Anna Baghdasaryan; Lisa Ofner-Ziegenfuß; Carolin Lackner; Peter Fickert; Bernhard Resch; Nicholas Mark Morris; Andrea Deutschmann (BMC, 2020)
Abstract Background Idiopathic or transient neonatal cholestasis (TNC) represents a group of cholestatic disorders with unidentified origin and remains a diagnosis of exclusion. Dysfunction of hepatobiliary transporters mediating excretion of biliary constituents from hepatocytes may play a central role in the pathogenesis of cholestasis. Despite variants of bile salt (BS) export pump (BSEP/ABCB11) have already been described in TNC, the pathogenic role of BSEP dysfunction in TNC remained so far elusive. Case presentation We report on a newly-identified heterozygous ABCB11 missense variant (c.1345G > A, p.Glu449Lys) which was associated with prolonged cholestasis in a term infant after a complicated neonatal period. Moreover, we show for the first time almost completely abolished BSEP expression on the hepatocellular membrane in TNC. Conclusion This report demonstrates for the first time a close association between the prolonged cholestasis in infancy and impaired BSEP expression on the hepatocyte canalicular membrane in a heterozygous carrier of newly-identified ABCB11 variant.